KONFLIK PERAN GANDA WAITRESS DALAM UPAYA MENINGKATKAN OPERATIONAL F&B SERVICE DI HOTEL MELIA BALI - Ni Kadek Eni Juniari; Ni Luh Suastuti; Ni Ketut Mustiya Liyani (Program Studi Manajemen Divisi Kamar, 2023)
The purpose of this study is to find out the number or absence of dual role conflicts felt by waitresses at Hotel Melia Bali and efforts to minimize the conflict of the dual role as an effort to improve Operational F&B Service at Hotel Melia Bali. The research method carried out is qualitatively descriptive. The data collection techniques used are questionnaires and interviews with data processing techniques looking for mean values and percentage scores using micrsoft excel software. In this study, 32 waitress respondents with the status of married and have children. The results showed that most waitresses at Hotel Melia Bali felt a dual role conflict in both Work-Family Conflict (WFC) / Family Conflict – Workers and Family-Work Conflict (FWC) / Family Conflict - Workers. This is seen from the results of data processing that shows a mean value of 3.63 with high interpretation and a percentage score of 83% indicating the criteria for the most part. This is seen from the average results of each indicator, namely conflict based on time, conflict based on pressure, conflict based on behavior, quality of work, quantity of work and timeliness. As the end of the study, the author conveyed advice to hotel Melia Bali to set up a daycare at an affordable rate aimed at waitresses who have children under five and can hold activities in the form of family gatherings by including children and husbands for waitresses who have a family. This can be a means for the hotel to get to know the family of the waitresses and is a means to bring closer the relationship between employees and their families.